Radon Concentrations in Indoor and Outdoor Environments of Atomic Energy Centre Dhaka, Bangladesh, and Concomitant Health Hazards - Pervin, Shikha; Yeasmin, Selina; Khandaker, Mayeen Uddin; Begum, Afia (Frontiers in Nuclear Engineering, 2022)
Realizing the non-negligible health hazards due to radon exposure, the present study was carried out to measure the radon concentrations in indoor and outdoor environments of Atomic Energy Centre Dhaka (AECD), Bangladesh. A portable electrostatic radon-measuring device (RAD7) was used to determine the indoor radon levels in different laboratories of AECD, anda RAD7 detector with stainless steel soil probe wasemployed to measure the soil gas radon in the surrounding areas of AECD campus. The indoor radon concentration in various laboratories was found to vary from 11.0 ± 7.3 Bq/m3 to 360 ± 180.38 Bq/m3 with an average of 62.71 ± 32.76 Bq/m3. Overall, the average indoor radon level shows below the action level (300 Bq/m3) recommended by ICRP publication-126 for homes and workplaces. However, the laboratories having poor ventilation show a relatively higher radon level. The average soil gas radon concentration at different depths of 15 cm, 35 cm, and 55 cm was found to be 0.07±0.01 kBq/m3, 2.31 ± 0.31 kBq/m3, 22.47±1.38 kBq/m3, respectively. The calculated average annual effective dose due to the inhalation of indoor radon for home and workplaces was found to be below the ICRP recommended value of 10 mSv/y present results could serve as a reference radon level in the indoor and outdoor environment in Dhaka city, Bangladesh.